Complexity analysis of FDE receivers for massive MIMO block transmission systems. Issue 12 (1st July 2019) - Pereira, Andreia; Bento, Pedro; Gomes, Marco; Dinis, Rui; Silva, Vitor
Abstract : This study considers massive multiple‐input multiple‐output (m‐MIMO) schemes employing orthogonal frequency division multiplexing (OFDM) or single‐carrier with frequency‐domain equalisation (SC‐FDE) modulation, concerning an uplink transmission. The authors study the performance and complexity for both conventional zero forcing (ZF) and minimum mean squared error (MMSE) (which require the inversion of channel matrix) and iterative frequency domain equalisation receivers based on equal gain combining (EGC) and maximum ratio combining (MRC) concepts, that do not require matrix inversions. It is shown that, although matrix inversions are generally the more complex operations for relatively balanced systems (i.e. with similar number of transmit and receive antennas), this is not generally true for systems where the channel matrix is 'very tall' (i.e. much more receive than transmit antennas), at least in terms of the number of multiplications and sums. This means that the advantage on a reduced complexity of MRC/EGC‐based equalisers with respect to ZF/MMSE is, in fact, limited. However, the performance advantages combined with the possibility of parallel receiver implementations, make those techniques particularly interesting for m‐MIMO schemes, either employing OFDM or SC‐FDE modulations.